Exploring Gender-Based Differences in Academic Performance: Insights from Accounting Students at A State University in Sri Lanka - Tharsika, K.; Varanitha, S.; Thaneshan, G. (University of Jaffna, 2024)
Purpose: Several studies have identified gender as a factor influencing academic performance, but the findings on the factors that explain the performance gap between genders remain inconclusive. Thus, this study investigates the factors contributing to differences in academic performance between male and female students in the Bachelor of Business Administration Honors in Accounting program at a State University in Sri Lanka. Design/Methodology/Approach: The study employs a quantitative approach by distributing questionnaires to accounting specialization students at a selected university to explore the reasons behind gender-based academic performance differences. A total of 87 fully completed questionnaires were received from respondents. Descriptive statistics and a one-sample t-test were used to analyze the data and address the research questions. Findings: The study revealed that personal commitment and attitude are crucial factors in academic achievement. Female students were generally excellent due to stronger work ethic, increased class participation, and more frequent interactions with lecturers. In contrast, male students often struggle with balancing academic responsibilities and social life, which impacts performance. Research limitations: The research is confined to accounting specialization students at a selected state university in Sri Lanka, which may restrict the applicability of the findings to other disciplines or institutions. Implications: The study highlights the need for tailored academic support to address gender-specific challenges in the learning process. Educational institutions should consider strategies that enhance male students' engagement, balancing academic and social responsibilities, while fostering female students' strengths in participation and commitment. This approach can bridge the academic performance gap and improve overall educational outcomes.
Keywords: Accounting performance; Gender gap; Study habits; Accounting students; Sri Lanka